2010
DOI: 10.1007/s00005-009-0055-4
|View full text |Cite
|
Sign up to set email alerts
|

Serodiagnostic Efficacy of Mycobacterium tuberculosis 30/32-kDa Mycolyl Transferase Complex, ESAT-6, and CFP-10 in Patients with Active Tuberculosis

Abstract: Elimination of tuberculosis (TB) largely depends upon definitive rapid diagnosis and treatment. Widely used diagnostic tests do not qualify for use in a developing country due to lack of either desired accuracy or their cost. In the present study an enzyme-linked immunosorbent assay was used to evaluate the diagnostic potential of an immuno-dominant 30/32-kDa mycolyl transferase complex (Ag85 complex) and Mycobacterium tuberculosis-specific proteins (ESAT-6 and CFP-10) of the RD1 region. Higher sensitivity (84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 40 publications
(39 reference statements)
2
15
0
Order By: Relevance
“…There are several new diagnostic techniques, such as nucleic acid amplification and immune reactions based on the cell-mediated immune response (10). Detection of antibodies using serodiagnostic tests is a rapid, easy-to-perform, user-friendly method which does not require a living cell.…”
mentioning
confidence: 99%
“…There are several new diagnostic techniques, such as nucleic acid amplification and immune reactions based on the cell-mediated immune response (10). Detection of antibodies using serodiagnostic tests is a rapid, easy-to-perform, user-friendly method which does not require a living cell.…”
mentioning
confidence: 99%
“…Similarly, all strains shown to export CFP-10 at high levels were virulent, whereas strains with less CFP-10 in supernatants were avirulent. ESAT-6 and CFP-10 have been reported to be strong targets for humoral and cell-mediated immune response (11). RV3615, also known as ESX-1 substrate protein C (ESPC), is a highly immunodominant RD1-dependent secreted antigen specific for MTB infection (12).…”
Section: Discussionmentioning
confidence: 99%
“…A study done in China [10] reported a sensitivity and specificity of 66.7% and 81.8%, respectively for ESAT-6-CFP-10 antigen. Another study from India reported a sensitivity and specificity of 64.9% and 88.9% for rESAT-6 and 66% and 85.2% for rCFP-10 antigen, respectively [18]. In these studies, they used healthy controls to determine specificity which might have resulted in a higher specificity [7].…”
Section: Discussionmentioning
confidence: 99%